Debt Report 2020 Edition II - World Bank (World Bank, Washington, DC, 2020)
This is the second of a new series of Debt Reports for 2020 to be published online, at regular intervals, over the course of the year. Debt Report 2020 Edition II is published at a time when many countries are struggling to cope with the deadly impact of COVID-19 and a large part of the global economy is shut down, generating both demand and supply side shocks. It is too soon to assess what the economic and financial costs will be, much less predict the impact on capital flows. However, learning from past global crises, low- and middle-income countries face serious risks. Pre-COVID-19 debt inflows from private creditors were forecast as subdued on account of the downturn in the global economy in 2019 and pre-crisis projections are for only a moderate recovery in 2020. This crisis is putting even more pressure on global economic growth and capital flows. As always in times of crisis, the World Bank and the IMF have stepped up to the plate, pledging a total of $62 billion of fast-disbursing funds to support low- and middle-income countries to mitigate the impact of the virus. They have issued a joint communique calling on official bilateral creditors in G20 countries to suspend debt payments from any of the world’s poores t countries that request forbearance, to allow time for an assessment of the impact of the crisis and the possible debt relief needs of each country. The aim of these Debt Reports is to provide users with analyses of evolving trends and developments related to external debt and public debt in individual countries and regional groups, with primary emphasis on low- and middle-income countries, and to keep users abreast of debt-related issues and initiatives.